2017
DOI: 10.15763/issn.2376-5275.2017.3.1.24-54
|View full text |Cite
|
Sign up to set email alerts
|

Reading Books and Reading Minds: Differential Effects of Wonder and The Crossover on Empathy and Theory of Mind

Abstract: We tested sixth graders for empathy and theory of mind before and after an academic unit on either Wonder or The Crossover. Wonder was associated with improved perspective-taking; students who read The Crossover increased in concern for others. Faux pas detection increased in both genders with Wonder, and in girls with The Crossover. Students who read The Crossover in print showed improved understanding of facial expressions, while students who used iPads declined. Young adult fiction is associated with improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…Oliver and Sapey's social model of disability (1999), is fundamental to the view that mental ill-health, due to its socially restrictive nature, should be viewed as a social problem that can be ameliorated through education, attitudinal change and social adjustment (Mertens et al, 2011). Empirical studies show behavioural change after reading fictional literature including increased empathy and pro-social behaviours as well as improved social cognitive skills (Deshpande, 2012;Guarisco et al, 2017;Johnson, 2012). According to Chance (2014), narratives that are well-written, complex stories and that reflect the lives of today's adolescents provide readers with an authentic reflection of the world many now inhabit.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Oliver and Sapey's social model of disability (1999), is fundamental to the view that mental ill-health, due to its socially restrictive nature, should be viewed as a social problem that can be ameliorated through education, attitudinal change and social adjustment (Mertens et al, 2011). Empirical studies show behavioural change after reading fictional literature including increased empathy and pro-social behaviours as well as improved social cognitive skills (Deshpande, 2012;Guarisco et al, 2017;Johnson, 2012). According to Chance (2014), narratives that are well-written, complex stories and that reflect the lives of today's adolescents provide readers with an authentic reflection of the world many now inhabit.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that the reading medium does not affect transportation when reading a modern story, but that transportation is disturbed when reading a traditional story digitally. Further, while the general interest in the text does not seem to depend on the reading medium (Grimshaw, Dungworth, McKnight, & Morris, 2007; Moyer, 2011), the effect of the reading medium on empathy and theory of mind are also ambiguous (Mangen & Kuiken, 2014; Guarisco et al, 2017). Kaakinen et al (2018), however, concluded that far too little is known about the emotional and cognitive aspects of digital reading.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The vast majority of studies addressing differential outcomes of reading in print versus reading on screen has focused on informational texts such as school books or expository texts and on the effects on a reader's understanding of such texts. Apart from a number of notable exceptions (e.g., Guarisco, Brooks, & Freeman, 2017; Haddock, Foad, Saul, Brown, & Thompson, 2019; Mangen, Olivier, & Velay, 2019), the literature so far has neglected (1) the reception of narrative and fictional e‐books for leisure reading and (2) the potential effects of digital reading on a broader conception of the reading experience. While informational texts may be primarily concerned with generating understanding of the information presented, we argue that reading literature during leisure time is about more than just text comprehension.…”
mentioning
confidence: 99%
“…Die einzigen Wissenschaftler*innen, die ihre Testpersonen teilweise selbst wählen ließen, welches von zwei vorher ausgewählten Büchern und ob sie dieses analog oder auf einem iPad lesen wollten, waren Guarisco, Brooks und Freeman (2017, 29ff) 23 . Sie gingen davon aus, dass sie auf diese Weise am besten untersuchen könnten, wie sich das Lesen von erzählerischen Texten auf die Theory of Mind und die Empathiefähigkeit von Schüler*innen auswirken.…”
Section: Spezifika Narrativer Texte Als Untersuchungsgegenstandunclassified